Sulfated silica-titania aerogel as a bifunctional oxidative and acidic catalyst in the synthesis of diols - Ling, Lee Siew; Hamdan, Halimaton (Elsevier B.V., 2008)

(untitled)
Sulfated silica-titania aerogel (SO4/ST) catalyst was prepared by direct synthesis and modified with H2SO4 by wet impregnation method. BrÃ¸nsted acid sites were generated after sulfation of the silica-titania aerogel with a pKa of -14.52. Consecutive transformation of 1-octene, catalyzed by sulfated silica-titania aerogel using aqueous hydrogen peroxide as oxidant shows high activity towards 1,2-octanediol through the formation of 1,2-epoxyoctane. The formation of 1,2-octanediol is enabled by the co-existence of sulfated Ti species with BrÃ¸nsted acid sites in the SO4/ST system. Sulfated silica-titania aerogel catalyst produced 1,2-octanediol (326 Î¼mol) with selectivity of 63%. In contrast, no diol was produced when silica-titania aerogel was used.